Primary Aldosteronism: State-of-the-Art Review - Vaidya, Anand; Hundemer, Gregory L; Nanba, Kazutaka; Parksook, Wasita W; Brown, Jenifer M (American journal of hypertension, 2022)
We are witnessing a revolution in our understanding of primary aldosteronism (PA). In the past 2 decades, we have learned that PA is a highly prevalent syndrome that is largely attributable to pathogenic somatic mutations, that contributes to cardiovascular, metabolic, and kidney disease, and that when recognized, can be adequately treated with widely available mineralocorticoid receptor antagonists and/or surgical adrenalectomy. Unfortunately, PA is rarely diagnosed, or adequately treated, mainly because of a lack of awareness and education. Most clinicians still possess an outdated understanding of PA; from primary care physicians to hypertension specialists, there is an urgent need to redefine and reintroduce PA to clinicians with a modern and practical approach. In this state-of-the-art review, we provide readers with the most updated knowledge on the pathogenesis, prevalence, diagnosis, and treatment of PA. In particular, we underscore the public health importance of promptly recognizing and treating PA and provide pragmatic solutions to modify clinical practices to achieve this.